IL-17A Levels and Progression of Kidney Disease Following Hospitalization with and without Acute Kidney Injury - Jason A. Collett; Alexander H. Flannery; Lucas J. Liu; Tomonori Takeuchi; David P. Basile; Javier A. Neyra (Kidney360)
Key Points. IL-17A was higher in patients with AKI versus without AKI during hospitalization and up to 1-year postdischarge. IL-17A was higher in patients with progression of kidney disease but not independently associated with subsequent progression of kidney disease. Background. AKI is associated with increased mortality and new or progressive CKD. Inflammatory cells play an important role in acute organ injury. We previously demonstrated that serum IL-17A levels were significantly elevated in critically ill patients with AKI and independently associated with hospital mortality. We hypothesize that IL-17A levels are elevated in hospitalized patients with AKI at diagnosis, and sustained elevation after discharge is associated with subsequent CKD incidence or progression. Methods. This was an observational convenience sampling study of hospital survivors of stage 2 or 3 AKI and controls without AKI from the Assessment, Serial Evaluation, and Subsequent Sequelae of AKI study. Patients were classified as progression or nonprogression on the basis of a composite of CKD incidence, progression, or ESKD. IL-17A levels were evaluated with S-Plex assay (Meso Scale Discovery) at 0 (during hospitalization), 3, and 12 months postdischarge and analyzed along with clinical and biomarker data up to 84 months after discharge. Results. Among 171 AKI and 175 non-AKI participants, IL-17A levels were elevated in AKI versus non-AKI patients at 0-, 3-, and 12-month time points (P < 0.05 for all comparisons). Furthermore, IL-17A levels were elevated in the progression versus nonprogression group at the 3- and 12-month time points for outcomes occurring at 3–6 and 12–84 months, respectively (P < 0.05 for both). In adjusted multivariable models, IL-17A levels were not independently associated with progression of kidney disease. IL-17A levels were positively correlated with kidney disease and immune activation biomarkers at all time points (P < 0.001). Conclusions. IL-17A was higher in patients with AKI versus without AKI during hospitalization and up to 1-year postdischarge. IL-17A was higher in patients with progression of kidney disease after hospitalization, but not independently associated with subsequent progression of kidney disease in fully adjusted models.